Mad church disease : overcoming the burnout epidemic - Jackson, Anne, 1980- (Grand Rapids, Mich. : Zondervan, 2009)
"Mad Church Disease, born out of that experience, is a lively, informative, and potentially life-saving resource for anyone in ministry-vocational or volunteer-who would like to understand, prevent, or treat the epidemic of burnout in church culture."--Jacket.
Foreword / by Craig Groeschel -- How to use this book -- Prologue: No pity parties here -- Introduction -- Part I: How the burnout epidemic is killing the greatest call -- Comparing mad cow disease to mad church disease -- The emergency -- Part II: Am I at risk? : examining risk factors and symptoms -- Internal risk factors -- External risk factors -- Symptoms -- Part III: Getting better -- Five principles of recovery -- Part IV: A path to health and recovery -- Spiritual health -- Physical health -- Emotional health -- Relational health -- Processing through pain -- Epilogue: Resting in an abundant life -- Notes -- Acknowledgements.
Includes bibliographical references (p. 185-187).
Keywords: Burn out (Psychology) -- Religious aspects -- Christianity